2020
DOI: 10.1007/978-981-15-1133-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Policy Interventions on Marine Social-Ecological Systems: Case Study of Sekisei Lagoon, Southwest Japan

Abstract: Using a case of the Sekisei Lagoon, Okinawa Prefecture, the southeastern tip of Japanese archipelago, this chapter discussed the interrelationships among the sectoral policy interventions by various marine-related ministries, and the whole structure of the integrated ocean policy. First, we developed the Social-Ecological Systems (SES) Schematic, which summarized the main ecosystem structures, functions, use types, and the stakeholders relating to the Sekisei Lagoon. Then, sectoral policy interventions by vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In light of this, integrated intervention with synergetic effects is urged under the current state of ecosystem decline accelerated by climate change (Makino et al2020;Morrison et al 2020). This should be taken into consideration by national and prefectural governments but has not been easy in Japanese oceanrelated policy arenas (Wakita and Yagi 2013;Wakita 2018;Makino et al 2020). To promote such transformative change of coral reef governance, it is desirable that the findings of this paper will be reached by not only local and national policy makers but also by more diverse stakeholders such as citizens and private companies, as suggested by recent works on the transnational, multiscale governance of Anthropocene reefs (Gurney et al 2017;Bellwood et al 2019;Morrison et al 2020).…”
Section: From Plural Valuation Of Nature Toward Transformative Governancementioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, integrated intervention with synergetic effects is urged under the current state of ecosystem decline accelerated by climate change (Makino et al2020;Morrison et al 2020). This should be taken into consideration by national and prefectural governments but has not been easy in Japanese oceanrelated policy arenas (Wakita and Yagi 2013;Wakita 2018;Makino et al 2020). To promote such transformative change of coral reef governance, it is desirable that the findings of this paper will be reached by not only local and national policy makers but also by more diverse stakeholders such as citizens and private companies, as suggested by recent works on the transnational, multiscale governance of Anthropocene reefs (Gurney et al 2017;Bellwood et al 2019;Morrison et al 2020).…”
Section: From Plural Valuation Of Nature Toward Transformative Governancementioning
confidence: 99%
“…For the identification of "key stakeholders," i.e. those with close connections to marine conservation, we referred to past works (Hori et al 2017;Makino et al 2020) as well as ethnographic fieldworks that have been conducted by the first author since 2009. After the identification of the targeted groups, participants were selected in consideration of their willingness to attend the Workshop and availability given the limited period of fieldwork.…”
Section: Data Collectionmentioning
confidence: 99%
“…Taking Japan as an example, the birth place of the Satoyama and Satoumi concepts, the local residents of Shiretoko Peninsula in Hokkaido have become a vital part of the traditional water ecosystem in the area, positively maintaining the interactive effects between humans and the natural ecosystem [4]. A study of the Sekisei Lagoon in southwest Japan revealed that in the local lagoon socio-ecological systems, all stakeholders are closely connected at the socio-ecological level and completely linked to the lagoon's ecosystem services, where traditional users have a critical role to play in the sustainability of socio-ecological systems [5]. Therefore, the sea or ocean and coastal ecosystems have a close and complex connection with local users.…”
Section: Introductionmentioning
confidence: 99%
“…Such bay areas and their adjacent coastal regions comprise a multifaceted social-ecological system (SES) that involves a diverse set of stakeholders (individuals, groups, or organizations that are (or will be) affected, involved, or interested (positively or negatively) by planning, development, and management [2]) and an ecosystem that is the foundation of natural resources (including water, fishery resources, and landscapes) [3]. The SES in the bay plays a vital role in supporting human activities in the surrounding hinterland.…”
Section: Introductionmentioning
confidence: 99%